2020
DOI: 10.1016/j.jsxm.2020.08.011
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of the Sexual Well-Being of New Parents with Community Couples

Abstract: Background Changes in sexual well-being are common for new mothers and their partners after the birth of a baby. However, most research has sampled mothers not couples, assessed only one aspect of sexual well-being, and has not included a control sample of couples. Aim This study aimed to compare the sexual well-being (ie, sexual frequency, sexual satisfaction, sexual desire, sexual distress) of first-time mothers and their p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 50 publications
1
11
0
Order By: Relevance
“…Consistent with our hypothesis, mothers’ sexual distress improved significantly over time, and by 12‐months postpartum was no longer above the clinical cutoff. This finding is in line with past research, which found less pronounced differences in sexual distress between new parents at 12‐months postpartum and control couples, compared to 3‐months postpartum (Schwenck et al., 2020). The clinical cutoff reflects a score that best distinguishes women with and without sexual dysfunction.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Consistent with our hypothesis, mothers’ sexual distress improved significantly over time, and by 12‐months postpartum was no longer above the clinical cutoff. This finding is in line with past research, which found less pronounced differences in sexual distress between new parents at 12‐months postpartum and control couples, compared to 3‐months postpartum (Schwenck et al., 2020). The clinical cutoff reflects a score that best distinguishes women with and without sexual dysfunction.…”
Section: Discussionsupporting
confidence: 92%
“…Although research on postpartum sexual distress specifically is scarce, the few studies in this area suggest that it is indeed prevalent. In a cross‐sectional study, Schwenck, Dawson, Muise, and Rosen (2020) found that new parent couples reported higher sexual distress at each of 3‐, 6‐, and 12‐months postpartum compared to community couples. Further, a recent longitudinal study following 203 new parent couples from mid‐pregnancy to 12‐months postpartum revealed that mothers reported consistently higher sexual distress than their partners over time.…”
Section: Sexual Distress In the Postpartum Periodmentioning
confidence: 99%
“…Similar to prior studies (Schwenck et al, 2020;Rossi et al, 2022), sexual desire was assessed using two equivalent sexual desire items from either the International Index of Erectile Function (IIEF; Rosen et al, 1997) for men (i.e., "Over the past 4 weeks, how often have you felt sexual desire? "; "Over the past 4 weeks, how would you rate your level (degree) of sexual desire?")…”
Section: Sexual Desirementioning
confidence: 99%
“…Additionally, by 3-months postpartum, most couples have resumed sexual activity (Lurie et al, 2013) and longitudinal studies sampling couples from pregnancy to 12-months postpartum reveal that sexual desire, sexual satisfaction, and relationship satisfaction are lowest at 3-months postpartum (Leonhardt et al, 2022; Rosen et al, 2020). Further, women who gave birth report significantly lower sexual desire and sexual satisfaction than their partners at 3-months postpartum, suggesting that they experience unique biopsychosocial changes and stressors compared to their partners (Schwenck et al, 2020).…”
Section: Systemic Transactional Model and Dyadic Coping In The Transi...mentioning
confidence: 99%